2022
DOI: 10.3389/fmicb.2021.793345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analyses of Clavibacter michiganensis Type Strain LMG7333T Reveal Distinct Gene Contents in Plasmids From Other Clavibacter Species

Abstract: Clavibacter michiganensis, a Gram-positive, plant-pathogenic bacterium belonging to Actinobacteria, is a causal agent of bacterial canker in tomatoes. Although LMG7333T is the type strain of C. michiganensis, it has not been used in many studies, probably because of a lack of the complete genome sequence being available. Therefore, in this study, the complete genome sequence of this type strain was obtained, and comparative genome analysis was conducted with the genome sequences of two other C. michiganensis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Clavibacter michiganensis it is a gram-positive bacterium [56]. this bacterium affects mainly the xylem vessels on the plants [57].…”
Section: Discussionmentioning
confidence: 99%
“…Clavibacter michiganensis it is a gram-positive bacterium [56]. this bacterium affects mainly the xylem vessels on the plants [57].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Thapa and co-workers (Thapa et al, 2017) showed that certain CAZymes (Carbohydrate-Active Enzymes) families involved in cellulose and hemicellulose degradation are abundant in the C. michiganensis genome. Although these previously identified pathogenicity factors have been unambiguously shown to be related to the development of the disease, there is also evidence that some of these factors are absent from strains capable of causing symptoms of the disease (Oh et al, 2022;Tancos et al, 2015) and that virulent strains can infect tomato plants without leading to symptoms (Gitaitis, 1991). Together, these observations suggest that other factors are required for triggering the disease and symptom development (Sharabani et al, 2013(Sharabani et al, , 2014.…”
Section: Introductionmentioning
confidence: 98%
“…translucens strains have been obtained, and the T3Es were identified, giving an insight into the pathovar-specific population structure (Shah et al, 2021). The comparative genome analysis of Clavibacter michiganensis, the causal agent of bacterial canker in tomatoes, shows the distinct gene contents in the plasmids (Oh et al, 2022). The first R. solanacearum genome GMI1000 was sequenced in 2002 and has been widely utilized in R. solanacearum studies (Salanoubat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%